Marketing System Development in Agribusiness of the Republic of Kazakhstan - KARABASSOV, Rassul Asylbekovich; RUSTEMBAEV, Bazarkhan Ergeshovich; KASKATAYEV, Nurlan Meyrambekovich; HAPOVA, Alyona Viktorovna; NURTAEVA, Zhanara Shansharovna (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
Nowadays the main impetus for the development of the economy of the country is the state of and prospects for the development of small and medium-sized businesses. Agriculture is a strategically important complex of the country, and therefore the development of small and medium precisely in the agricultural sector is a priority of solving the food security of the state as a whole, and each region - in particular. The relevance of the article is related to the importance and priority of the role of small and medium-sized businesses in the state economy. Small and medium-sized businesses an incentive to economic development, the state of this sector depends on the well-being of the population and the country as a whole. Small and medium enterprises can be created in any area of the economy. The object of the study is organizational and economic relations arising in the implementation of the state support of small and medium-sized businesses in the agricultural sector. Presented by the author's definition of the definition of ‘efficiency of the state support of small and medium-sized businesses in the agricultural sector.’ The study presents the author's definition of state support as a measure of the effectiveness of achieving the goal of the state with the most full use of the conditions and factors allocated to achieving the goal of the subject of small or medium-sized businesses determine this measure. Achievement of the goals and objectives was provided by the following scientific methods: economic and statistical, abstract and logical, dialectical and historical analysis and synthesis, as well as macro- and microeconomic methods of analysis of economic phenomena and processes. The study was also used in the works of classical economic theory, well-known scientists of Agricultural Economists, legal acts regulating the activities of the agro-industrial complex of mills, statistical materials and supplies publications in mass media, Internet resources.
Keywords: marketing, agribusiness, development, operation, Kazakhstan, the structure, the monetary value